Primary health information standard system based on semantic interoperability - Zhao, Xia (BMC Med Inform Decis Mak, 2018)
BACKGROUND: To realize semantic interoperability for Primary Health Information System (PHIS), this study analyzes and applies existing health information data standards in China. This research aims to establish a Primary Health Information Standard System (PHISS), and achieve the semantic level interoperability and application of primary health information. METHODS: First, the PHISS in accordance with the structural standards of national information standards system in China was constructed. Second, application of semantic interoperability level with reference to the interoperability model was standardized. Thirdly, referring to the data element model, PHIS data element dictionary with good interoperability is developed by standardizing data element attributes of identifiers, names, definitions and permissible value. Fourthly, based on PHIS data element dictionary, PHIS dataset is developed following the relevant rules for health information datasets. RESULTS: PHISS is composed of basic class standards, data class standards, technical class standards, security and privacy class standards, management class standards. In this study, we reorganized the data class standards that meet the requirements of PHIS, also develops and adds PHIS data element, PHIS data element dictionary and PHIS dataset. PHIS data element dictionary includes 16 parts and PHIS dataset includes 22 parts, which satisfies the data standardization requirements of PHIS. CONCLUSIONS: The establishment of the PHISS can meet the needs for the interconnection of the residents’ basic health service information and realize the semantic level interoperability of various information services. The key steps of this method are based on semantic interoperability. Relevant data elements and datasets with semantic interoperability are selected. Moreover, an information standard system is constructed, and the information standardization requirements of the PHIS are met.